Autonomic Dysfunctions in Parkinsonian Disorders - Hyo-Jin Bae; Sang-Myung Cheon; Jae Woo Kim (Journal of Movement Disorders, 2009)
Background and Purpose: Symptoms of autonomic dysfunctions are common in the patients with parkinsonian disorders. Because clinical features of autonomic dysfunctions are diverse, the comprehensive evaluation is essential for the appropriate management. For the appreciation of autonomic dysfunctions and the identification of differences, patients with degenerative parkinsonisms are evaluated using structured questionnaire for autonomic dysfunction (ADQ). Methods: Total 259 patients, including 192 patients with [idiopathic Parkinson’s disease (IPD, age 64.6 ± 9.6 years)], 37 with [multiple system atrophy (MSA, 62.8 ± 9.1)], 9 with [dementia with Lewy body (DLB, 73.9 ± 4.3)], and 21 with [progressive supranuclear palsy (PSP, 69.4 ± 9.6)]. The ADQ was structured for evaluation of the presence of symptoms and its severity due to autonomic dysfunction, covering gastrointestinal, urinary, sexual, cardiovascular and thermoregulatory domains. Patients were also evaluated for the orthostatic hypotension. Results: Although dementia with Lewy body (DLB) patients were oldest and duration of disease was longest in IPD, total ADQ scores of MSA and PSP (23.9 ± 12.6 and 21.1 ± 7.8) were significantly increased than that of IPD (15.1 ± 10.6). Urinary and cardiovascular symptom scores of MSA and gastrointestinal symptom score of PSP were significantly worse than those of IPD. The ratio of patient with orthostatic hypotension in IPD was 31.2% and not differed between groups (35.1% in MSA, 33.3% in DLB and 33.3% in PSP). But the systolic blood pressure dropped drastically after standing in patients with MSA and DLB than in patients with IPD and PSP. Conclusions: Patients with degenerative parkinsonism showed widespread symptoms of autonomic dysfunctions. The severity of those symptoms in patients with PSP were comparing to that of MSA patients and worse than that of IPD.